2022
DOI: 10.1111/jfb.15028
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niche of Australian cownose rays (Rhinoptera neglecta) and whitespotted eagle rays (Aetobatus ocellatus) along the east coast of Australia

Abstract: Australian cownose rays (Rhinoptera neglecta) and whitespotted eagle rays (Aetobatus ocellatus) are large myliobatiform rays that co‐occur off temperate eastern Australia. Here, we performed stable‐isotope analyses (δ13C, δ15N and δ34S) on fin clips of both species to gain insights into their trophic interactions and isotopic niches, and assess the effect of preservation (ethanol‐stored versus frozen) on isotopic values of fin‐clip tissue of R. neglecta. Linear mixed models identified species as the main facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…These contrasting visit patterns may be a result of interspecific competition due to their shared semipelagic nature and likely comparable trophic levels confirmed via overlapping isotopic niches observed in Australian cownose rays ( Rhinoptera neglecta ) and spotted eagle rays ( A . ocellatus ) [ 66 ] and similar diet compositions [ 6 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting visit patterns may be a result of interspecific competition due to their shared semipelagic nature and likely comparable trophic levels confirmed via overlapping isotopic niches observed in Australian cownose rays ( Rhinoptera neglecta ) and spotted eagle rays ( A . ocellatus ) [ 66 ] and similar diet compositions [ 6 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that while the δ 15 N values differed among species, there may not be a substantial ecological significance as the observed maximum difference (1.5‰) did not exceed the general discrimination factor of 3.4‰ for δ 15 N (Post, 2002 , but see Hussey et al., 2014 ). Samples from green turtles also had the widest ranges for δ 13 C, δ 15 N, and δ 34 S (Table 1 ), which may suggest that they use a wider range of resources and exhibit higher variability in diet and habitat type, and thus may be more generalists (Chan et al., 2022 ). This is further supported by their larger niche size estimate compared with the other species.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies to date that use bulk isotope ratios to characterize marine turtle niches focus on carbon (δ 13 C) and nitrogen (δ 15 N) (Haywood et al., 2019 ). However, the addition of a third isotopic marker, sulfur (δ 34 S), can provide additional insights since δ 34 S isotope ratios exhibit limited trophic fractionation and can be used to determine differences between benthic and pelagic productivity pathways in coastal systems (Chan et al., 2022 ; García‐Vernet et al., 2021 ; Peterson & Fry, 1987 ). This is because primary producers that use different sources of sulfur will have different δ 34 S values (Connolly et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent dietary data suggest the two species exhibit only modest niche overlap (37). A recent isotopic study suggested Aetobatus is less trophically constrained than Rhinoptera, possibly due to its larger size, gape, and buccal morphology, allowing it to exploit a wider range of prey (38). In Florida's Indian River Lagoon, the two genera occupy similar spaces, although visitation patterns to the same habitats are asynchronous (26).…”
Section: Ecological Considerationsmentioning
confidence: 99%